Clustering The Duplicate Open Crash Reports Based on Call Stack Traces of Crash Reports - Pushpalatha, MN; Mrunalini, M (International Journal of Computer Sciences and Engineering, 2018)
A computer program such as software application that stops functioning properly is called software crash. Software crash is tedious problem in software development environment. Upon user permission, the crash report which contains the stack traces is sent to the developer or vendor. Software development team receives hundreds of crash reports from many deployment sites. There are many duplicate crash reports are generated, because many users submit the crash reports for the same problem. For analysing each crash reports, it may take more time. This motivates, to present the solution to analyse the crash reports and cluster the duplicate crash reports based on call stack similarities and store them into unique bucket, so that development resources can be optimized. In this paper, clustering the duplicate crash report of open source is proposed based on the similar information in the call stack. Hierarchical clustering technique is used to cluster the duplicate crash reports into unique bucket. Mozilla and Firefox open source crash reports are used for experiment and performance evaluation is done using purity determined the purity of clusters up to 80%. This method helps to increase the efficiency and reduce the number of developers along with an improved time to fix the bug.